Assessing the potential of managed aquifer recharge using rooftop rainwater harvesting with shallow wells in peri-urban communities in Kumasi, Ghana - P. Amihere-Ackah; I. Monney; D. C. Okyere; K. A. Adjei; E. K. Appiah-Adjei (Discover Water)
Abstract In many cities worldwide, groundwater levels have declined significantly due to climate change and increased water demand, necessitating artificial recharge. This study explores the potential of Managed Aquifer Recharge (MAR) using Rooftop Rainwater Harvesting Systems (RRWHS) to replenish groundwater in peri-urban communities in Kumasi, Ghana. Specifically, it estimates the response of groundwater levels to RRWHS, evaluates the potential groundwater recharge due to RRWHS, and assesses the groundwater quality. Six hand-dug wells were selected, four equipped with RRWHS (MAR wells) and two serving as controls. Over 12 months, groundwater levels were monitored using Van Essen Conductivity (CTD) divers, while rainfall data were obtained from the Trans-African Hydro-Meteorological Observatory (TAHMO). The Water Table Fluctuation method was used to assess recharge rates, and 50 water samples were analysed for physicochemical and microbial contamination. More than 500 m3 of rainfall was effectively harvested and infiltrated into the aquifer. The wells for MAR-RRWHS significantly increased groundwater levels, with median recharge of 231 mm, about three times higher than control wells (97 mm). The wells for MAR-RRWHS responded rapidly to rainfall with consistent recharge values, serving as recharge points for other wells. However, control wells recharged more gradually and inconsistently. Chemical analysis showed that in wells for MAR, harvested rainwater diluted nitrates but increased turbidity immediately after a rainfall event due to turbulence from direct infiltration. Despite these challenges, the study highlights the positive impact of MAR-RRWHS on groundwater recharge. The findings suggest that MAR-RRWHS can be a sustainable solution for groundwater recharge in water-scarce regions. Further research is needed to optimise water quality and long-term effectiveness.